Reoperation for bleeding after cardiac surgery. Issue 5 (3rd September 2022) - De La Porte, Vincent M.; De Meyer, Gregory R. A.; Schepens, Tom; Verbrugghe, Walter; Laga, Steven; Allegaert, Mathias; Mertens, Pieter; Rodrigus, Inez; Jorens, Philippe G.
Abstract: Background: Postoperative cardio-surgical haemostatic management is centre-specific and experience-based, which leads to a variability in patient care. This study aimed to identify which postoperative haemostatic interventions may reduce the need for reoperation after cardiac surgery in adults. Methods: A retrospective case-control study in a tertiary centre. Adult, elective, primary cardiac surgical patients were selected ( n = 2098); cases ( n = 42) were patients who underwent reoperation within 72 h after the initial surgery. Interventions administered to control surgical bleeding were compared for the need to re-operate using multiple logistic regression. Results: Rate of cardiac surgical reoperation was 2% in the study population. Three variables were found to be associated with cardiac reoperation: preoperative administration of fresh frozen plasma (OR 5.45, CI 2.34-12.35), cumulative volume of chest tube drainage and cumulative count of packed red blood cells transfusion on ICU (OR 1.98, CI 1.56-2.51). Conclusion: No significant difference among specific types of postoperative haemostatic interventions was found between patients who needed reoperation and those who did not. Perioperative transfusion of fresh frozen plasma, postoperative transfusion of packed cells and cumulative volume of chest tube drainage were associated with reoperation after cardiac surgery. These variables could help predict the need for reoperation.